ON THE CLASSIFICATION OF INTERNATIONAL ANTI-CORRUPTION DOCUMENTS - Zhanat Askarovna, Мамитова (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
The article deals with the classification of international anti-corruption instruments direction, the analysis and the importance of each document for the criminal - law policy of the Republic of Kazakhstan.